2020
DOI: 10.3389/fpsyg.2020.01131
|View full text |Cite
|
Sign up to set email alerts
|

Older Adults’ Conduct of Everyday Life After Bereavement by Suicide: A Qualitative Study

Abstract: Background: The loss of a loved one to suicide can be a devastating experience that can have negative long-term effects on the social life and physical and mental health of the bereaved person. Worldwide, an estimated 237 million older adults have experienced suicide bereavement. As assumed in critical psychology, "the conduct of everyday life" reflects the social self-understanding by which people actively organize their lives based on their personal concerns, negotiation with co-participants in various actio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…The description of suicide as an incomprehensible act was in the core of these perceptions. The participants, desolated by the nature of the loss, were engaged in incessant thoughts about the event as they could not find any satisfactory reason for it (Barnes, 2006; Begley & Quayle, 2007; Dutra et al, 2018; Entilli et al, 2021; Hybholt et al, 2020; Kawashima & Kawano, 2017; Lee et al, 2019; Lindqvist et al, 2008; Ross et al, 2018; Shields et al, 2019; Sugrue et al, 2014; Tzeng et al, 2010; Wainwright et al, 2020). Most of the times, the need for evidence and fulfilling answers was not met; even the existence of a suicide note was not enough to provide satisfactory answers to the family members regarding the reasons why their loved one was driven to suicide.
It was question after question.
…”
Section: Resultsmentioning
confidence: 99%
“…The description of suicide as an incomprehensible act was in the core of these perceptions. The participants, desolated by the nature of the loss, were engaged in incessant thoughts about the event as they could not find any satisfactory reason for it (Barnes, 2006; Begley & Quayle, 2007; Dutra et al, 2018; Entilli et al, 2021; Hybholt et al, 2020; Kawashima & Kawano, 2017; Lee et al, 2019; Lindqvist et al, 2008; Ross et al, 2018; Shields et al, 2019; Sugrue et al, 2014; Tzeng et al, 2010; Wainwright et al, 2020). Most of the times, the need for evidence and fulfilling answers was not met; even the existence of a suicide note was not enough to provide satisfactory answers to the family members regarding the reasons why their loved one was driven to suicide.
It was question after question.
…”
Section: Resultsmentioning
confidence: 99%
“…Many were driven to participate in communities with their peers, found strong connections and new belongings to a group. These are important anchors for coping with later-life challenges [ 7 ]. Groos and Shakespeare-Finch’s [ 33 ] evaluation of peer support groups for suicide bereavement found that an effortful thought process and the level of pain experienced were temporal and dependent on the individual’s own post-trauma trajectory or meaning-making process.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of studies found that none fulfilled the inclusion criteria [ 6 ]. Hyboldt et al’s [ 7 ] subsequent qualitative empirical study investigated the age-related factors for participants during the post-bereavement restoration process and their re-orientation to life after such a devastating loss. The lack of theoretical and methodological consistency in suicide and ageing research has also been noted [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Internal and external influencing factors (e.g., trauma, stigma, and loss of autonomy) may result in fleeting non-specific thoughts with no significant (active) wish to die or reflect chronic yet passive suicidal thoughts that do not elevate risk of actual suicide. Further studies comparing bereavement experiences of those bereaved by suicide in later life with other traumatic bereavements and losses will also help understand the individual experiences and pathways within suicide research to help inform and enrich assessments and interventions in aging care (Hybholt et al, 2020 ; Hafford-Letchfield et al, 2022b ).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, however, people with an existential sense of completed life, or a wish to die, are less likely to be in touch with professionals, particularly clinicians (van Wijngaarden et al, 2019 ; Hafford-Letchfield et al, 2020 ). Further qualitative research on age-related factors on the traumatic impact of suicide bereavement (Hybholt et al, 2020 ) has demonstrated the relationship between grief and the lack of motivation to carry on and adapt to the physical and psychological effects of growing older. These impacts are also known to trigger suicidal thoughts and/or the wish for the hastening of the end of life (Hafford-Letchfield et al, 2022b ).…”
Section: Introductionmentioning
confidence: 99%